Dietary Modifications in Fissure-in-ano: A Qualitative Study Based on Persian Medicine - Tavakoli-Dastjerdi, Sedigheh; Tavakkoli-Kakhki, Mandana; Derakhshan, Ali R.; Teimouri, Azam; Motavasselian, Malihe (Current Nutrition & Food Science, 2020)
Background: Anal fissure (AF) is a common disease associated with severe pain and reduced quality of life. Factors related to lifestyle, including diet and bowel habits, play a pivotal role in its pathogenesis. Most of the chronic fissures are not responsive to drugs and more likely to recur. Given the significance of diet in Persian medicine (PM), investigation on physiopathology and appropriate foods can be useful for decreases in AF symptoms and consequences. Objective: This study was intended to evaluate the role of diet in the formation and progression of AF from the perspective of PM. Methods: In this study, the most important resources of PM dating back to thousands of years were reviewed. All these textbooks contained a section on AF, its causes, and treatment. Further analysis was performed on these resources in comparison with databank and resources of modern medicine to develop a food-based strategy for AF management. Results: From the view of PM, the warmth and dryness of anus temperament accounted for AF. Both Persian and modern medicine identified constipation as another cause for AF. Therefore, avoidance from some foods and commercial baked goods was recommended. Both Persian and modern medicine forbad the following foods: potato, cabbage, cauliflower, pasta, beef, fish, and so forth. High fiber and oligo-antigen diets with some limitations have garnered more attention. Conclusion: An integrative approach is recommended employing both Persian and modern medicine for AF. There have been some evidence in this regard, however standardized clinical trials are required for future research.
Keywords: fissure-in-ano